2004
DOI: 10.1126/science.1099190
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mode of Epothilone A on α,ß-Tubulin by Electron Crystallography

Abstract: The structure of epothilone A, bound to alpha,beta-tubulin in zinc-stabilized sheets, was determined by a combination of electron crystallography at 2.89 angstrom resolution and nuclear magnetic resonance-based conformational analysis. The complex explains both the broad-based epothilone structure-activity relationship and the known mutational resistance profile. Comparison with Taxol shows that the longstanding expectation of a common pharmacophore is not met, because each ligand exploits the tubulin-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
430
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(457 citation statements)
references
References 26 publications
21
430
1
5
Order By: Relevance
“…The benzoyl phenyl residues of epothilone A were shown to reside in a region of the β-tubulin pocket that is not occupied by paclitaxel. Moreover, four out of the five oxygen-containing polar groups within epothilone A have unique contacts with the β-tubulin protein that are not shared by paclitaxel (34). Three unique molecular interactions were identified that are critical to epothilone A binding with β-tubulin pocket.…”
Section: Epothilonesmentioning
confidence: 94%
See 1 more Smart Citation
“…The benzoyl phenyl residues of epothilone A were shown to reside in a region of the β-tubulin pocket that is not occupied by paclitaxel. Moreover, four out of the five oxygen-containing polar groups within epothilone A have unique contacts with the β-tubulin protein that are not shared by paclitaxel (34). Three unique molecular interactions were identified that are critical to epothilone A binding with β-tubulin pocket.…”
Section: Epothilonesmentioning
confidence: 94%
“…Three unique molecular interactions were identified that are critical to epothilone A binding with β-tubulin pocket. Threonine 274 and arginine 282 of β-tubulin form cooperative hydrogen bonds with the C3, C5, and C7 oxygens of epothilone A that are necessary for binding (34). In addition, glutamine 292 of β-tubulin forms a hydrogen bond with leucine 275 that is essential to stabilization of the M loop conformation and cooperative hydrogen bonding to epothilone A (34).…”
Section: Epothilonesmentioning
confidence: 99%
“…In addition to its topological role in mediating lateral and longitudinal interactions in microtubule assembly (26), it forms part of the binding site for paclitaxel and other drugs that stabilize microtubules (7,39), is close to the vinblastine binding site (16), and undergoes a sizable conformational shift when tubulin assembles into microtubules (13). It is also located near fenestrations in the microtubule wall, prompting the suggestion that this loop may control the entry of paclitaxel to its binding site in the microtubule lumen (40).…”
Section: Discussionmentioning
confidence: 99%
“…the response of cells transfected with mutant h-tubulin to colcemid and vinblastine, two drugs that inhibit microtubule assembly but bind to distinct sites on tubulin (13,16), and to paclitaxel and epothilone A, two microtubulestabilizing agents that bind to a third site (7,39). Examples of the dose-response curves are shown in Supplementary Fig.…”
Section: Cells Resistant To One Drug Show Collateral Sensitivity To Tmentioning
confidence: 99%
“…As a new class of potentially chemotherapeutic drugs, epothilone and related compounds have demonstrated good anti-tumor activity in cell lines and tumor models (19,20). Furthermore, many synthetic compounds that possess a similar structure to the epothilone-derived [( S , E )-2-methyl-1-(2-methylthiazol-4-yl) hexa-1,5-dien-ol] (MMHD) may cross the blood brain barrier in mice and rats, indicating their potential value in the treatment of primary and secondary brain tumors and MS, all of which represent brain diseases associated with proliferative processes (21 -24).…”
Section: Introductionmentioning
confidence: 99%